The lost boys - Schumacher, Joel, 1939-2020; Feldman, Corey; Gertz, Jami; Haim, Corey, 1971-2010 (Burbank, CA : Warner Home Video, 1998)
When a string of mysterious deaths occur after they move to a coastal California town, teenagers Mike and Sam become convinced that their new home is overrun with vampires.
Originally released as a motion picture in 1987.
Features: production notes, theatrical trailer.
Corey Feldman, Jami Gertz, Corey Haim, Edward Herrmann, Barnard Hughes, Jason Patric, Kiefer Sutherland, Dianne Wiest.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English with optional English, French, or Spanish subtitles.
Keywords: Teenagers -- California -- Drama; Vampires -- Drama; Video recordings for the hearing impaired; Fiction films; Feature films; Horror films; Vampire films